Neither exogenous, nor endogenous: Evidence for a distinct role of negative emotion during attentional control - Xiaojuan Xue; Gilles Pourtois (PLoS ONE, 2025)
Negative or threatening stimuli capture attention. However, it remains unclear whether this phenomenon is best conceived as bottom-up (i.e., salience-driven) or top-down (i.e., goal-directed) instead. To address this question, we conducted two experiments using a previously validated dot-probe task (DPT) where physical salience (i.e., abrupt luminance change) and negative emotion (i.e., fearful face) competed with one another for attention selection (Experiment 1, n = 40) or negative (but also positive) emotion could be used as an endogenous cue by the participants to guide this process (Experiment 2, n = 39). Eye-tracking was used to ascertain that both cue and target were processed with peripheral vision. In Experiment 1, we found that negative emotion and physical salience both drove spatial attention in a bottom-up manner, yet their effects were under-additive, suggesting that they could mutually inhibit each other. Moreover, the results of Experiment 2 showed that fear, unlike happiness, could bias spatial attention in a top‑down manner, but only when participants were aware of the association created between the emotional cue and target’s location, leading to an enhanced validity effect in the high probability condition but an invalidity effect in the low probability one. Combined together, these novel findings suggest that negative value does not influence the priority map independently from physical salience and goal but depending on the specific combination of cues available for attention selection in the environment, it acts either as an exogenous or endogenous cue, thereby revealing an enhanced flexibility for it.